Chimera hypermedia for heterogeneous software development enviroments. - Anderson, Kenneth M. (ACM transactions on information systems.)
Emerging software development environments are characterized by heterogeneity: they are composed of diverse object stores, user interfaces, and tools. This paper presents an approach for providing hypermedia services in this heterogeneous setting. Central notions of the approach include the following: anchors are established with respect to interactive views of objects, rather than the objects themselves; composable, n-ary links can be established between anchors on different views of objects which may be stored in distinct object bases; viewers may be implemented in different programming languages; and, hypermedia services are provided to multiple, concurrently active, viewers. The paper describes the approach, supporting architecture, and lessons learned. Related work in the areas of supporing heterogeneity and hypermedia data modeling is discussed. The system has been employed in a variety of contexts including research, development, and education.